Is silver a mere terminal oxidant in palladium catalyzed C–H bond activation reactions?. Issue 1 (13th November 2019) - Bhaskararao, Bangaru; Singh, Sukriti; Anand, Megha; Verma, Pritha; Prakash, Prafull; C, Athira; Malakar, Santanu; Schaefer, Henry F.; Sunoj, Raghavan B.
Abstract : We disclose an intriguing and a potentially general role for one of the most commonly used silver salt additives whose molecular understanding continues to remain rather vague in the contemporary practice of palladium catalysis. Abstract : In the contemporary practice of palladium catalysis, a molecular understanding of the role of vital additives used in such reactions continues to remain rather vague. Herein, we disclose an intriguing and a potentially general role for one of the most commonly used silver salt additives, discovered through rigorous computational investigations on four diverse Pd-catalyzed C–H bond activation reactions involving sp 2 aryl C–H bonds. The catalytic pathways of different reactions such as phosphorylation, arylation, alkynylation, and oxidative cycloaddition are analyzed, with and without the explicit inclusion of the silver additive in the respective transition states and intermediates. Our results indicate that the pivotal role of silver salts is likely to manifest in the form of a Pd–Ag heterobimetallic species that facilitates intermetallic electronic communication. The Pd–Ag interaction is found to provide a consistently lower energetic span as compared to an analogous pathway devoid of such interaction. Identification of a lower energy pathway as well as enhanced catalytic efficiency due to Pd–Ag interaction could have broad practical implications in the mechanism of transition metal catalysis and the current perceptions on the same.